The Hidden Power of Dreams : An Essential Guide to Interpreting Your Dreams - Royston, Robin (London Bantam Press, 2006)
Draws on the real-life experiences of people who have had unusual and disturbing dreams. The author describes how, when we dream, we slip into a hidden world where nature takes control and where the dream holds the key to understanding. He shows us how to approach decoding our dreams, and explores how our inner mind can unlock our creative depths.
Include Noted, Bibliography and Index
Keywords: Dreams